THE ANTI-INFLAMMATORY ACTIVITY OF ESSENTIAL OIL OF CLOVE (Syzygium aromaticum) IN ABSORPTION BASE OINTMENT WITH ADDITION OF OLEIC ACID AND PROPYLENE GLYCOL AS ENHANCER - SUGIHARTINI, NINING; PRABANDARI, RANI; YUWONO, TEDJO; RAHMAWATI, DESTY RESTIA (International Journal of Applied Pharmaceutics, 2019)
Background : The optimal concentration of essential oil of clove in absorption base ointment as anti-inflammatory has been studied. The development of formulations can be done by adding oleic acid and propylene glycol as enhancers. The purpose of this study was to determine the anti-inflammatory activity of the essential oil of clove in absorption base ointment formula by adding a mixture of oleic acid and propylene glycol as enhancers. Methods: In this study, the composition of oleic acid and propylene glycol was 100% oleic acid (FI), 50% oleic acid and propylene glycol (FII), and 100% propylene glycol (FIII). The profile of the anti-inflammatory activity essential oil of clove was carried out using male of mice Balb/C strain which was induced inflammatory with croton oil on back of skin. After treatment, it was sacrificed and then was taken the back of skin to get histopathological preparation. After that, the epidermal thickness, number of inflammatory cells, and cyclooxygenase (COX)-2 expression can be measured. Results : Based on the results of the test, it shows that FIII has the smallest of the amount of COX-2 expression, the number of inflammatory cells, and the epidermal thickness so the addition of the composition enhancer provides good anti-inflammatory activity. Conclusion: The increasing concentration of propylene glycol caused the raising activity of essential oil of clove as anti-inflammatory.